Tata Kelola Perusahaan Dan Pengungkapan Sukarela (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2023)
This study examines the correlation between corporate governance and voluntary disclosure of information. The sample used was companies that conducted an IPO on the Indonesia Stock Exchange in 2018. Using purposive sampling technique, 129 data were obtained. The analytical tool used was multiple regression analysis with SPSS version 25. The study found that the number of board of directors influenced voluntary disclosure of information, while foreign  ownership, institutional ownership, management  ownership, public share ownership, independent commissioners, and audit committees were not found to influence voluntary disclosure.GCG, . voluntary disclosure, foreign   ownership, institutional ownership